Ginger essential oil nanoemulsion composite film, preparation method thereof and application of ginger essential oil nanoemulsion composite film in cherry tomato preservation

By combining ginger essential oil nanoemulsion with natural materials such as chitosan and sodium caseinate, and using tannin as a crosslinking agent, a ginger essential oil nanoemulsion composite membrane was developed, which solved the problem of non-biodegradation and insufficient performance of materials in the existing fruit preservation technology, and achieved efficient fruit preservation effect.

CN119856735APending Publication Date: 2025-04-22SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070904.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the existing fruit preservation technology, synthetic packaging materials are not biodegradable and may release toxic substances, and packaging materials such as chitosan and sodium caseinate still have room for improvement in mechanical properties and barrier properties.

Method used

A ginger essential oil nano-emulsion composite membrane was developed. By combining ginger essential oil with natural materials such as chitosan and sodium caseinate, tannin acid is used as a crosslinker to improve the mechanical properties, barrier properties and UV resistance of the membrane.

Benefits of technology

The ginger essential oil nano-lactte composite membrane significantly delays the spoilage of cherry tomatoes, especially inhibits the invasion of mold, improves the mechanical properties, barrier properties and UV resistance of the membrane, and extends the shelf life of the fruits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856735A_ABST
    Figure CN119856735A_ABST
Patent Text Reader

Abstract

The invention discloses a ginger essential oil nanoemulsion composite film, a preparation method thereof and application of the ginger essential oil nanoemulsion composite film in cherry tomato preservation. Chitosan, sodium caseinate and ginger essential oil nanoemulsion are used as raw materials to prepare the antibacterial fresh-keeping composite film. By analyzing the physicochemical properties and microbial properties of the cherry tomatoes in the process of being stored for 15 days, the shelf life of the cherry tomatoes is prolonged by about 6 days through the coating of the composite film, and the growth of fungi is not observed within 15 days. Meanwhile, the cherry tomatoes keep the lowest weight loss rate of 3.49% and the highest hardness of 14.08 N, the titratable acidity of 21.99 g / kg and the soluble solid content of 6.73%. The inhibition area of the composite film on the growth of cherry tomato hyphae reaches 50.27 mm < 2 >. The ginger essential oil nanoemulsion composite film has great application potential in fruit preservation, and provides a natural and antibacterial substitute for traditional fruit packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fruit preservation, and in particular to a ginger essential oil nanoemulsion composite film and a preparation method thereof and application thereof in cherry tomato preservation. Background Art

[0002] Fresh fruits are damaged by fungi and pathogenic microorganisms during post-harvest transportation and storage. At the same time, factors such as oxidation and water loss will affect the quality and shelf life of fruits. Generally, various films are used as barrier materials to effectively isolate air and microorganisms to extend the shelf life of fruits (e.g., PE plastic films). However, synthetic packaging materials have many disadvantages, such as non-biodegradability and release of toxic substances. In recent years, functional coatings have become an effective, convenient, green and sustainable method for fruit preservation. Proteins and polysaccharides are considered to be potential alternative packaging materials due to their biodegradability, excellent film-forming properties, low cost and availability. By forming a translucent film on the surface of fruits with polysaccharide and protein polymers, a multifunctional barrier can be established to reduce mechanical damage, inhibit gas exchange and prevent microbial infection.

[0003] Chitosan is a natural polymer derived from chitin, which has good antibacterial, antioxidant and enzyme inhibition activities. The free amino-hydroxyl groups in chitosan give it gel-forming properties and easy film-forming properties, but the mechanical properties and barrier properties of the packaging materials prepared from it still need to be improved. Sodium caseinate (SC) is derived from dairy products, and its film-forming properties are attributed to the generated intermolecular electrostatic interactions, hydrogen bonds and hydrophobic interactions. Although the film incorporating caseinate has better durability and stability against thermal denaturation and coagulation. However, due to the relatively high hydrophilicity of sodium caseinate, its water vapor barrier properties are poor. Tannic acid (TA) is a natural cross-linking agent widely present in many plants and has certain antibacterial activity, antioxidant activity and UV resistance. Because TA has polyphenolic hydroxyl groups, it can form hydrogen bonds and covalent bonds with amino or hydroxyl groups in proteins and polysaccharides, thereby improving the cohesion and stability of the film.

[0004] Tomato is a world-famous plant because of its unique benefits for human health and nutrition. In particular, cherry tomatoes (Lycopersicon esculentum var.Cerasiforme A.Gray) are highly appreciated worldwide for their good flavor, small size and health benefits. In terms of total output value, cherry tomatoes are the second most important vegetable crop in the world, containing rich nutritional compounds, including carotenoids, ascorbic acid, total phenols and flavonoids. Cherry tomatoes, like other seasonal fruits, need to pay attention to the quality effects of ripening and respiration during storage, and microbial infection is also a place that needs attention. Due to China's warm and humid climate, cherry tomatoes are susceptible to attacks by various microorganisms such as Aspergillus, Alternaria, and Fusarium, resulting in spoilage. In addition, contamination by Penicillium and Aspergillus ochraceus can also lead to corruption during storage. Therefore, it is very necessary to develop cherry tomato packaging protective films for antibacterial effects.

[0005] Plant essential oils have significant antibacterial effects and have been widely used in the preservation of fruits and vegetables in recent years. There are also many reports on the use of plant essential oils in thin films for fruit preservation, such as sodium alginate-sodium carboxymethyl cellulose composite films loaded with clove essential oil for blueberry preservation, gelatin-chitosan films loaded with green tea essential oil microcapsules for strawberry preservation, chitosan-sodium starch octenyl succinate films loaded with fennel seed essential oil for apple preservation, and chitosan-pullulan films loaded with artemisia annua essential oil for grape preservation. Ginger essential oil (GEO) is a volatile oily substance extracted from the rhizome of ginger. A large number of studies have shown that ginger essential oil has excellent antibacterial activity. Edible coatings developed based on essential oil nanoemulsions have become a new sustainable fruit preservation method. Therefore, the development of composite films based on GEO nanoemulsions as antibacterial active substances has great application potential in fruit preservation. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing a ginger essential oil nanoemulsion composite film.

[0007] Another object of the present invention is to provide a ginger essential oil nanoemulsion composite film obtained by the above preparation method.

[0008] Another object of the present invention is to provide an application of the ginger essential oil nanoemulsion composite film.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a ginger essential oil nanoemulsion composite film comprises the following steps:

[0011] (1) Preparation of ginger essential oil nanoemulsion

[0012] The ginger essential oil is added into water, and an emulsifier is added during homogenization to form a crude emulsion; the crude emulsion is crushed to obtain a ginger essential oil nanoemulsion;

[0013] (2) Preparation of chitosan / sodium caseinate mixture

[0014] Chitosan is dissolved in glacial acetic acid solution and stirred to obtain a completely dispersed chitosan solution; sodium caseinate is dispersed in distilled water under stirring and continuously stirred to obtain a sodium caseinate solution; the two solutions are mixed and stirred to obtain a chitosan / sodium caseinate mixed solution;

[0015] (3) Preparation of ginger essential oil nanoemulsion composite film

[0016] The ginger essential oil nanoemulsion obtained in step (1) is added to the chitosan / sodium caseinate mixed solution obtained in step (2) and stirred; tannic acid is then added and stirred; finally, a plasticizer is added, stirred, and ultrasonic degassing is performed to obtain a film-forming solution of a ginger essential oil nanoemulsion composite film.

[0017] Furthermore, the amount of ginger essential oil added in step (1) is calculated based on its concentration in the system of 2±0.5 w / v%.

[0018] Furthermore, the homogenization treatment described in step (1) is achieved by a high-speed shearing machine under the following conditions: rotation speed 12000±1000rpm, time 2±0.5min.

[0019] Furthermore, the emulsifier described in step (1) is Tween 80.

[0020] Furthermore, the mass ratio of the emulsifier to the ginger essential oil in step (1) is 1:2 to 1:4, preferably 1:3.

[0021] Furthermore, the disruption described in step (1) is achieved by an ultrasonic cell disruptor under the following conditions: ice water bath, power 400±50W, ultrasonic time 12±2min, continuous 4±1s, interval 4±1s. The ultrasonic process is carried out in an ice water bath to prevent overheating.

[0022] Furthermore, the amount of chitosan added in step (2) is calculated based on its concentration in the chitosan solution being 1±0.5 w / v%.

[0023] Furthermore, the glacial acetic acid in step (2) is a glacial acetic acid solution with a concentration of 1±0.5 w / v%.

[0024] Furthermore, the amount of sodium caseinate added in step (2) is calculated based on its concentration in the sodium caseinate solution of 2±0.5 w / v%.

[0025] Furthermore, the volume ratio of the chitosan solution to the sodium caseinate solution in step (2) is 1:2 to 2:1, preferably 1:1.

[0026] Furthermore, the amount of the ginger essential oil nanoemulsion added in step (3) is calculated based on a concentration of 10 v / v% to 20 v / v% in the system; preferably, it is calculated based on a concentration of 20 v / v% in the system.

[0027] Furthermore, the amount of tannic acid added in step (3) is calculated based on its concentration in the system of 0.5±0.1 w / v%.

[0028] Furthermore, the plasticizer described in step (3) is glycerol.

[0029] Furthermore, the amount of the plasticizer added in step (3) is calculated as 30±5% of the total mass of sodium caseinate and chitosan.

[0030] Furthermore, the stirring time in step (3) is 30±5 min.

[0031] Furthermore, the time of ultrasonic degassing in step (3) is 30±5 min.

[0032] Furthermore, in step (3), after obtaining the film-forming liquid of the ginger essential oil nanoemulsion composite film, the film-forming liquid is poured into a mold, dried, and peeled off to obtain the ginger essential oil nanoemulsion composite film.

[0033] A ginger essential oil nanoemulsion composite film is obtained by the preparation method.

[0034] Application of the ginger essential oil nanoemulsion composite film in fruit preservation.

[0035] Furthermore, the application is to spray the film-forming liquid of the ginger essential oil nanoemulsion composite film on the surface of the fruit, dry it naturally to form a film on the surface of the cherry tomatoes, and preserve it.

[0036] Furthermore, the fruit includes cherry tomatoes.

[0037] Furthermore, the longest storage period is 15 days.

[0038] Compared with the prior art, the present invention has the following advantages and effects:

[0039] In the GEO nanoemulsion composite film provided by the present invention, TA crosslinking improves the mechanical properties, barrier properties, UV resistance and thermal stability of the GEO nanoemulsion composite film. The GEO nanoemulsion composite film delays the corruption and deterioration of cherry tomatoes during storage, especially inhibits the infection of mold.

[0040] In addition, C / SC / TA / O20 The film showed excellent inhibitory effect on the spoilage fungus Fusarium oxysporum in cherry tomatoes.

[0041] In conclusion, the ginger essential oil nanoemulsion composite film of the present invention has great application potential in fruit preservation and provides a natural and antibacterial substitute for traditional fruit packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Figure 1 is a diagram of the preparation process of the composite membrane;

[0043] Figure 2 The characterization results of the composite film are shown in Figure 1 (hardness (A); tensile strength (B); elongation at break (C); water vapor permeability (D); transmittance at 200nm (E) and 600nm (F); infrared absorption spectrum (G); thermogravimetric analysis curve (TGA) (H); different letters represent significant differences (P < 0.05));

[0044] Figure 3 The scanning electron microscope observation images of the composite membranes (C / SC membrane (A); C / SC / O 10 Membrane (B); C / SC / O 20 Membrane (C); C / SC / TA membrane (D); C / SC / TA / O 10 Membrane (E); C / SC / TA / O 20 membrane (F));

[0045] Figure 4 This is a diagram showing the changes in appearance of cherry tomatoes during storage;

[0046] Figure 5 This is a graph showing changes in various indicators of cherry tomatoes during storage (weight loss rate (A), hardness (B), titratable acidity (C), and soluble solids content (D));

[0047] Figure 6 The graph shows the inhibitory effect of the composite film on Fusarium oxysporum (the inhibitory effect of the composite film on the culture medium on spoilage bacteria (A); the inhibitory effect of the composite film on hyphae growth (B); the area of ​​mycelium growth inhibited by the composite film (C); different letters represent significant differences (P < 0.05));

[0048] Figure 7 Phylogenetic tree constructed for MEGA 11 software. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0050] Materials used in the following examples: Ginger essential oil (GEO) was extracted using a low-temperature continuous phase change device; cherry tomatoes were purchased from a supermarket near South China Agricultural University (Guangzhou, China); chitosan, sodium caseinate, and tannic acid were purchased from Maclean Co., Ltd. (Guangzhou, China). Glycerol was purchased from Tianjin Yongda Chemical Reagent Co., Ltd. (Tianjin, China); potato dextrose agar medium (PDA) was purchased from Guangdong Huankai Biotechnology Co., Ltd. (Guangzhou, China); Ezup column fungal genomic DNA extraction kit and SanPrep column DNA gel recovery kit were purchased from Shanghai Shenggong Biotechnology Co., Ltd. (Shanghai, China); other reagents were analytically pure and commercially available.

[0051] In the following examples, w / v means g / mL, and v / v means mL / mL.

[0052] Example 1: Preparation of GEO nanoemulsion composite membrane

[0053] (1) Preparation of GEO nanoemulsion

[0054] 2% (w / v) GEO was added to primary water and homogenized for 2 min at 12000 rpm using a high-speed shearing machine to form a crude emulsion. Tween 80 was added during the homogenization process, and the mass ratio of Tween 80 to GEO was 1:3. The crude emulsion was disrupted with an ultrasonic cell disruptor to obtain a GEO nanoemulsion. The conditions of the ultrasonic cell disruptor are as follows: ultrasonic power 400w, ultrasonic 4s. Interval 4s, total time 12min, the ultrasonic process was carried out in an ice water bath to prevent overheating. The prepared GEO nanoemulsion was stored at 4°C for future use.

[0055] (2) Preparation of composite membrane

[0056] Chitosan (C) was dissolved in 250 mL of 1% (v / v) glacial acetic acid solution at a ratio of 1% (w / v), and stirred at room temperature overnight to obtain a completely dispersed chitosan solution. Sodium caseinate (SC) was dispersed in 250 mL of distilled water at a ratio of 2% (w / v) under magnetic stirring, and stirred continuously at room temperature for 2 h. The two solutions were mixed in a ratio of 1:1, and stirred for 30 min to obtain a C / SC mixed membrane-forming solution.

[0057] A total of 6 membranes are designed:

[0058] C / SC membrane: no additional materials are added;

[0059] C / SC / O 10 Membrane: 10% (v / v) GEO nanoemulsion was added to the C / SC mixture and stirred for 30 min;

[0060] C / SC / O 20Membrane: 20% (v / v) GEO nanoemulsion was added to the C / SC mixture and stirred for 30 min;

[0061] C / SC / TA membrane: Add 0.5% tannic acid (w / v) to the C / SC mixture and stir for 30 min;

[0062] C / SC / TA / O 10 Membrane: 10% (v / v) GEO nanoemulsion was added to the C / SC mixture and stirred for 30 min, followed by the addition of 0.5% tannic acid (w / v) and stirring for 30 min.

[0063] C / SC / TA / O 20 Membrane: 20% (v / v) GEO nanoemulsion was added to the C / SC mixture and stirred for 30 min, followed by the addition of 0.5% tannic acid (w / v) and stirring for 30 min.

[0064] Finally, all samples were added with glycerol as a plasticizer at 30% of the total mass of sodium caseinate and chitosan and stirred for 30 minutes. Ultrasonic degassing was performed for 30 minutes, and 20 mL of the film-forming solution was poured into a plastic culture dish (90 mm) and dried at room temperature (about 30°C) to remove the film. The film was placed under constant temperature and humidity (25±0.5°C, 50±5%RH) for 48 hours for use.

[0065] Example 2: Characterization of GEO nanoemulsion composite membrane

[0066] 1. Characterization of Composite Membranes

[0067] (1) Thickness measurement of composite films

[0068] The thickness of the film was measured with a micrometer (Shanghai Shenhan Measuring Instrument Co., Ltd., accuracy 0.001 mm). Five random points were selected for each sample and the average value was taken.

[0069] (2) Mechanical properties measurement of composite films

[0070] The film was cut into strips of 4 cm × 1.5 cm, and the tensile strength (TS) (Formula 1) and elongation at break (EAB) (Formula 2) of the film were measured using an electronic universal testing machine (UTM4204, Shenzhen Sansi Zongheng Technology Co., Ltd.). The test component spacing was 2 cm, and the tensile speed was 0.5 mm / s.

[0071]

[0072] Where TS is the tensile strength (MPa); F is the maximum tensile force received when the membrane breaks (N); S is the cross-sectional area of ​​the membrane (m 2 ).

[0073]

[0074] Where L0 is the length of the film when it breaks (cm); L is the initial spacing of the test parts of the film (cm).

[0075] (3) Measurement of light transmittance of composite films

[0076] The film was cut into rectangular pieces of 3 cm in height and 0.4 cm in width and attached to the inside of a quartz cuvette. The transmittance (A%) at 200 nm and 600 nm was measured using an ultraviolet spectrophotometer (UV-750, Shanghai Precision Scientific Instrument Co., Ltd.).

[0077] (4) Measurement of water vapor transmission rate (WVP) of composite films

[0078] At room temperature, add CaCl2 dried to constant weight to a dry constant weight crucible. Seal a film of a certain size at the mouth of the crucible and weigh it quickly. Place the weighed crucible in a glass desiccator with saturated sodium chloride at the bottom to form conditions of 25°C and 75% relative humidity. After 12 hours, take out the crucible and weigh it, and calculate WVP (Formula 3):

[0079] WVP=WlAtΔP(3)

[0080] Where, WVP (g·m -1 ·s -1 ·Pa -1 ) represents water vapor permeability; W represents the added mass of the crucible (g); l represents the thickness of the film (mm); A represents the area of ​​the film (m 2 ) ; t is the time taken for the mass of the crucible to increase (s); ΔP is the pressure difference on both sides of the membrane (Pa). Since the experiment was carried out at 25°C and the relative humidity was maintained at 75%, ΔP was taken as 2376.75 Pa.

[0081] (5) Fourier transform infrared spectroscopy analysis of composite films

[0082] The membrane was placed in a desiccator containing P2O5 for one week to remove as much water as possible. A 2 × 0.5 cm piece of membrane was then placed in the sample chamber and the resolution was set to 4 cm. -1 The scanning number was 64 times and the ambient temperature was 25°C. The Fourier transform infrared spectrometer (Vertex 70 Bruker) (500-4000cm -1 ) and then analyze the infrared spectrum.

[0083] (6) Thermal stability analysis of composite films

[0084] The thermal stability of the film was measured using a thermogravimetric analyzer (TG209F1LibraTM, NETZSCH Instrument Manufacturing Co., Ltd., Germany). The film was placed in a desiccator containing P2O5 for one week to remove as much moisture as possible. 8 mg of the sample was weighed and placed in a crucible. The initial temperature was set to 20°C, the final temperature was set to 800°C, and the heating rate was set to 15°C / min.

[0085] (7) Scanning electron microscopy (SEM) observation of composite membranes

[0086] Place the film in a dryer containing P2O5 for one week to remove as much moisture as possible. Take an appropriate area of ​​the film to be tested and cut it into strips of 5mm×2mm. Fix the film to the conductive glue on the sample stage and spray gold for about 30 minutes. Place the treated film sample under a scanning electron microscope (EVO MA 15ZEISS), set the acceleration voltage of the electron beam to 5kV, adjust the magnification, and capture the scanning electron microscope image of the film surface.

[0087] 2. Results:

[0088] (1) Preparation of composite membrane

[0089] Depend on Figure 1 It can be seen that the C / SC membrane is transparent, while the C / SC / TA membrane is dark brown. The addition of tannic acid makes the colors of the two membranes very different. The polyphenols in TA affect the color of the membrane. After GEO nanoemulsion is added to the C / SC membrane, the color turns yellow as the concentration of GEO nanoemulsion increases. On the contrary, after GEO nanoemulsion is added to the C / SC / TA membrane, the brown color becomes lighter. It is worth noting that all six groups of membranes have good foldability.

[0090] C / SC, C / SC / O 10 、C / SC / O 20 、C / SC / TA、C / SC / TA / O 10 、C / SC / TA / O 20 The thickness of the membranes were 0.057, 0.073, 0.082, 0.077, 0.08, and 0.089 mm, respectively. Tannic acid significantly increased the thickness because tannic acid made the cross-linking between the membrane matrix higher and tighter. In addition, the incorporation of GEO also increased the thickness of the membrane.

[0091] (2) Mechanical properties analysis of composite membranes

[0092] Depend on Figure 2 As shown in Figure B, the tensile strengths of C / SC and C / SC / TA films are 2.56MPa and 8.08MPa, respectively. Tannic acid crosslinking greatly increases the tensile strength of the composite film, which may be due to the large number of hydrogen bonds in tannic acid combined with chitosan and sodium caseinate, increasing the connection capacity of the film. 10、C / SC / O 20 、C / SC / TA / O 10 、C / SC / TA / O 20 The tensile strength of the membranes were 1.84, 1.60, 6.99, and 6.97 MPa, respectively. Whether it was C / SC or C / SC / TA membrane, the addition of GEO reduced the tensile strength of the membrane. This was mainly because GEO had a certain hydrophobicity, which reduced the polymerization of chitosan and sodium caseinate, and at the same time created certain gaps in the membrane, reducing the continuity of the composite membrane.

[0093] Depend on Figure 2 As shown in Figure C, although TA can increase the tensile strength of the composite film, it reduces the elongation at break (EA B) of the film. When the concentration of GEO nanoemulsion in the C / SC film increases from 0% to 20%, the elongation at break of the composite film increases from 11.82% to 32.86%. This indicates that the addition of GEO nanoemulsion increases the flexibility of the composite film to a certain extent. 10 There was no significant difference in the elongation at break between C / SC / TA / O 20 The above results show that the addition of GEO improves the elongation at break of the membrane, which may be because essential oils can increase the flexibility of composite membranes based on polysaccharides or proteins by interfering with the interaction between polymer chains.

[0094] (3) Water vapor transmission rate (WVP) of composite film

[0095] Depend on Figure 2 As shown in Figure 5, the WVP of C / SC film and C / SC / TA film are 7.97×10 -12 gm -1 s -1 Pa -1 and 3.85×10 -12 gm -1 s -1 Pa -1 It can be found that TA significantly reduced the WVP of the membrane (P < 0.05), which is because TA created a denser network structure in the membrane and reduced the transmission of water molecules. In addition, the increase in membrane thickness led to a longer path for water molecules to pass through, which is also one of the reasons for the reduction of WVP. C / SC / O 10 and C / SC / O 20 The WVP of the membranes were 9.03×10 -12 gm -1 s -1 Pa -1 and 9.87×10 -12 gm -1 s -1 Pa-1 , GEO increased the water vapor permeability of C / SC film. This is because the presence of essential oils hindered the interaction between polymer chains and reduced the degree of crosslinking, which led to an increase in the water vapor permeability of the film. On the other hand, although the hydrophobicity of GEO is beneficial to reducing the WVP of the membrane, the cavity structure it produces will increase the water vapor permeability more. Among all the membranes, C / SC / TA / O 20 The WVP of the membrane is the lowest, only 2.21×10 -12 gm -1 s -1 Pa -1 This is because the hydrophobicity of GEO hinders the transmission of water vapor, and TA makes the membrane tightly cross-linked, reducing the effect of essential oils in hindering the interaction of polymers. Therefore, tannic acid, as a cross-linking agent of the composite membrane, greatly improves the barrier properties of the membrane.

[0096] (4) Analysis of optical properties of composite films

[0097] Depend on Figure 2 As shown in Figures E and F, tannic acid significantly reduced the light transmittance of the composite film at 200nm and 600nm. The aromatic ring structure of TA provides it with a certain degree of UV resistance. The deepening of the film color may also be the reason for the reduction in transmittance. In addition, the addition of GEO reduced the light transmittance of the C / SC film, which may be because the essential oil promotes light scattering, thereby reducing the light transmittance of the film to varying degrees. In particular, the tiny oil droplets in the nanoemulsion may further enhance light scattering. It is worth noting that compared with the C / SC / TA film, the C / SC / TA / O 10 and C / SC / TA / O 20 The light transmittance of the film increased slightly, which may be due to the addition of GEO changing the color of the composite film and making it lighter. On the other hand, the essential oil may reduce the degree of polymerization of the film, resulting in an increase in light transmittance.

[0098] In general, TA is beneficial to improving the optical properties of the film and greatly reduces the light transmittance of the film, making its preservation application value higher. 10 and C / SC / TA / O 20 The light transmittance of the film is slightly higher, but compared with the C / SC film, its UV resistance is still better.

[0099] (5) Infrared spectroscopy analysis of composite films

[0100] Figure 2 The Fourier transform infrared spectra of the middle G show the chemical structure differences of the six groups of membranes. The C / SC / TA membrane has a peak at 763 cm -1 The characteristic peak appears at 1200 cm, which corresponds to the C=C bond of the benzene ring of tannic acid. -1The increase in the peak at 1342 cm-1 may be related to the CO stretching vibration in tannic acid, especially the CO bond in the phenolic hydroxyl group, indicating that TA was successfully incorporated into the membrane. In addition, the absorption peak in this area may also be related to the CN (Amide-III) stretching vibration, which is common in proteins. In the three groups of TA cross-linked membranes, the peak at 1342 cm-1 replaced the peak at 1318 cm-1. -1 The peak at 1342 cm-1 is attributed to the bending of the OH bond and the stretching of the CO bond. Since the tannic acid molecule contains multiple phenolic hydroxyl groups, hydrogen bonds may be formed between these functional groups or with the functional groups in chitosan and sodium caseinate, resulting in the appearance of absorption peaks in this region. In addition, the peak at 1342 cm-1 may also be related to the out-of-plane bending vibration of the benzene ring CH, because the tannic acid molecule contains a benzene ring structure. -1 、1544cm -1 and 1317cm -1 The peaks at correspond to C=O stretching (Amide I), NH bending (Amide II), and CN stretching (Amide III). The absorption peaks of Amide I and Amide II represent the β-sheet and α-helix in the SC structure, respectively. GEO has little effect on the overall peak shape, indicating that GEO has no covalent or other interactions with the membrane.

[0101] (6) Thermal stability analysis of composite films

[0102] Figure 2 The thermogravimetric analysis curve of H shows the weight change of the composite membrane at 25-800℃. The remaining weight of C / SC membrane is 22.45%, while that of C / SC / O 10 and C / SC / O 20 The weight loss of C / SC / TA membrane was 21.79% and 17.47% respectively. As the concentration of GEO nanoemulsion increased, the weight loss increased. After cross-linking with tannic acid, the remaining weight of C / SC / TA membrane was as high as 27.46%, and the weight loss of C / SC / TA / O 10 and C / SC / TA / O 20 The remaining weight of the membrane is also 25.28% and 23.29%. It can be seen that GEO increases the thermal loss of the membrane, because the essential oil is more unstable and volatile during the heating process under the same mass. Tannic acid improves the thermal stability of the membrane as a whole. Since tannic acid contains a large number of polyphenol structures, polyphenol compounds can produce thermosensitive free radicals through thermal conversion, resulting in the densification of the network structure between polymers, thereby improving thermal temperature resistance.

[0103] (7) Scanning electron microscopy observation of composite membranes

[0104] like Figure 3As shown in the figure, the surface of the C / SC film has obvious irregular cracks (A), on the contrary, the surface of the C / SC / TA film is tight (D). This is because tannic acid increases the interaction between the film-forming matrix. The incorporation of GEO causes a large number of cavities or oil droplets to aggregate on the surface of the film, and the cavities become larger with increasing concentration (B, C). These cavities are caused by the hydrophobicity of the essential oil in the film and the evaporation of the essential oil during the drying process due to the failure of the essential oil to be stably embedded in the film. The presence of a large number of cavity structures reduces the mechanical properties and barrier properties of the film. After tannic acid cross-linking, the number and size of cavities generated by GEO are reduced (E, F). In particular, when the concentration of GEO nanoemulsion is 10%, there are only tiny and a few cavities. This shows that under the cross-linking of tannic acid, the essential oil is well embedded in the tight membrane structure and is not easy to evaporate during the drying process. It also further proves that tannic acid cross-linking has a certain improvement on the mechanical properties and barrier properties of the film.

[0105] Example 3: Determination of the preservation effect of GEO nanoemulsion composite film on cherry tomatoes

[0106] 1. Determination of preservation effect

[0107] (1) Film coating of cherry tomatoes

[0108] Divide the intact cherry tomatoes of similar size into 4 groups, including C / SC / TA, C / SC / TA / O 10 and C / SC / TA / O 20 The cherry tomatoes in the group were sprayed with the corresponding film-forming liquid on the surface. The film-forming liquid was naturally dried to form a film on the surface of the cherry tomatoes. The non-sprayed treatment was used as the control group. The cherry tomatoes were stored in a PE plastic box with ventilation and room temperature, and various indicators were measured every 3 days.

[0109] (2) Determination of weight loss rate

[0110] Weigh the initial weight m1 of the cherry tomatoes on a 1 / 1000 balance, measure the weight m2 of the cherry tomatoes every 3 days, and calculate the weight loss rate (Formula 4).

[0111] Weight loss rate (%) = (m1-m2) / m1×100(4)

[0112] (3) Hardness measurement

[0113] The hardness (N) of cherry tomatoes was measured using a TA / 36R cylindrical probe of a texture analyzer (TA.new plus ISENSO). The measurement conditions were: pressing depth 5 mm, pressing speed 0.5 mm / s.

[0114] (4) Determination of titratable acid

[0115] Peel the cherry tomatoes and crush them to obtain a uniform mixture. Take 5g of the sample and add an equal amount of distilled water to mix. After centrifugation, take the supernatant and titrate it with NaOH (0.05M) to pH 8.2. Calculate the titratable acid content (Formula 5)

[0116]

[0117] Where: c: sodium hydroxide concentration, unit is mol / L; V1: volume of sodium hydroxide consumed in titration, unit is mL; V2: volume of sodium hydroxide consumed in blank test titration, unit is mL; F: dilution factor; m: mass of sample, unit is g

[0118] (5) Soluble solid content (SSC) analysis

[0119] After the cherry tomatoes were squeezed with gauze, the juice was centrifuged at 4000 rpm for 10 min. Three drops of the supernatant were dropped into a handheld refractometer (Chengdu Taihua Optical Company) to read the soluble solid content (%).

[0120] result:

[0121] According to the results of the characterization of the composite membrane, C / SC / TA, C / SC / TA / O 10 、C / SC / TA / O 20 The three films were used to investigate their effects on the preservation of cherry tomatoes. Figure 4 It can be seen that the composite film has a good film-forming effect on the surface of cherry tomatoes. In the early stage of storage, the appearance changes among the four groups were not much different. On the 12th day of storage, the control group showed mold contamination and corruption, while the other three groups did not show corruption. Until the 15th day, C / SC / TA and C / SC / TA / O 10 All groups were contaminated with mold, but the corruption area in the C / SC / TA group was larger. 20 The group did not show any contamination until 15 days, which extended the shelf life of cherry tomatoes by about 6 days. This shows that the C / SC / TA membrane itself has a certain antibacterial effect, and the antibacterial property of GEO makes the composite membrane more antiseptic, which is more conducive to preventing microbial contamination of cherry tomatoes.

[0122] (1) Weight loss rate

[0123] Depend on Figure 5 As shown in Figure A, the weight loss rate of cherry tomatoes gradually increased with time. The weight loss rate of the control group reached 6.28% on the 15th day. 10 、C / SC / TA / O 20The weight loss rates of the three groups were 4.68%, 4.39% and 3.49%, respectively, which were significantly lower than those of the control group (P < 0.05). The results showed that the C / SC / TA membrane had a certain effect in delaying the weight loss of cherry tomatoes, and the addition of GEO had a more obvious effect on slowing down the weight loss, especially the C / SC / TA / O 20 The weight loss rate of the group was about half of that of the control group on the 15th day. The membrane may have reduced the weight loss rate by inhibiting the respiration and microbial growth of cherry tomatoes.

[0124] (2) Hardness

[0125] Depend on Figure 5 From Figure B, we can see that from the 0th day to the 15th day, the hardness of the control group decreased from 19.38N to 7.79N, a decrease of about 60%. The decrease in hardness is related to the destruction of the cell wall. 10 、C / SC / TA / O 20 The hardness of the groups at the 15th day was significantly higher than that of the control group (P < 0.05), which were 11.27N, 12.78N, and 14.08N, respectively. As the concentration of essential oil increased, the hardness decreased more slowly. 20 The hardness of the group was only reduced by 27% at 15 days. This shows that the C / SC / TA series of films have a certain effect on maintaining the hardness of cherry tomatoes, especially the C / SC / TA / O 20 membrane.

[0126] (3) Titratable acidity

[0127] Depend on Figure 5 As shown in Figure C, the titratable acidity of the four groups of cherry tomatoes decreased with time, but the control group showed a more obvious downward trend, from 24.03 g / kg to 13.05 g / kg. The titratable acidity of cherry tomatoes is related to the organic acids such as ascorbic acid and citric acid in them. The decrease in acidity during storage can be attributed to the decomposition of organic acids caused by the respiration of the fruit. C / SC / TA / O 20 The titratable acidity of cherry tomatoes in the group with the highest titratable acidity was the highest, and there was no significant change during the entire storage process (P>0.05), and it was still 21.99 g / kg at 15 days. This shows that GEO plays a major role in maintaining the quality of cherry tomatoes, especially at high concentrations.

[0128] (4) Soluble solids content

[0129] Depend on Figure 5 As shown in Figure D, the soluble solid content decreased with time, especially in the control group, which decreased by about 50% from 0d to 15d, and was only 4.73% at 15d. 10、C / SC / TA / O 20 The soluble solids content of the groups were 5.57%, 5.87% and 6.73%, respectively, which were significantly higher than those of the control group (P < 0.05). The reduction in soluble solids content may also be related to the respiration and ripening of the fruit. This result also shows that the composite film has a certain effect on slowing down the ripening and respiration of cherry tomatoes, thereby extending their shelf life.

[0130] Example 4: Analysis of the inhibitory effect of GEO nanoemulsion composite membrane on spoilage bacteria

[0131] 1. Analysis of the inhibitory effect of composite membrane on spoilage bacteria

[0132] (1) Pick the spoilage bacteria from the corrupted parts of cherry tomatoes, streak them on PDA medium, and repeat 3 times to isolate the single colony of the spoilage bacteria. Use the Ezup column fungal genomic DNA extraction kit to extract the DNA of the strain, and use the fungal universal primers (NS1: GTAGTCATATGCTTGTCTC, NS6: GCATCACAGACCTGTTATTGCCTC) to amplify 18s rDNA. After the amplification results were detected by agarose gel electrophoresis, sequencing was performed at Shanghai Shenggong Biotechnology Co., Ltd. Sequence comparison was performed by the BLAST tool in the NCBI database (https: / / blast.ncbi.nlm.nih.gov / Blast.cgi), and the species sequence with the highest similarity was selected to construct a phylogenetic tree using MEGA 11 software to determine the species of the unknown bacteria.

[0133] (2) The isolated spoilage bacteria were inoculated in a potato glucose liquid medium and cultured at 30°C and 150 r / min for 48 h. Then, spore liquid was filtered through three layers of lens paper. After counting on a hemocytometer, the spore liquid was diluted with sterile water to a certain multiple for later use. 100 μL of the film-forming liquid (C / SC / TA, C / SC / TA / O 10 and C / SC / TA / O 20 ) as the experimental group, and sterile water as the blank control group. After drying, 100 μL of mold spore solution was inoculated to make the spore amount 1×10 6 Then the growth effect was observed after culturing at 30°C for 48 h.

[0134] A bacterial cake with a diameter of about 9 mm was inoculated in the middle of the PDA medium. The culture was carried out at 30°C for 48 h until the mycelium grew into a circle with uniform radius. Then, composite films (C / SC / TA, C / SC / TA / O 10 and C / SC / TA / O 20), and a sterile filter paper was used as a blank control. After continuing to culture at 30°C for 48 hours, the inhibition area of ​​the composite film on the growth of mycelium was calculated.

[0135] result:

[0136] (1) Isolation and identification of spoilage bacteria

[0137] The spoilage bacteria were selected from the cherry tomatoes in the control group and single colonies were isolated by streaking three times on PDA medium. The sequence was determined by 18s rDNA and uploaded to the NCBI database (GenBank: PP979141). The phylogenetic tree was constructed by selecting the 27 species sequences with the highest similarity in the NCBI database using MEGA 11 software. It was found that the best homology was with Fusarium oxysporum ( Figure 7 ). Therefore, it was preliminarily determined that the spoilage bacteria isolated from cherry tomatoes in this study were Fusarium oxysporum.

[0138] (6) Composite membrane inhibitory effect on spoilage bacteria

[0139] Depend on Figure 6 As shown in Figure A, the C / SC / TA membrane has a slight inhibitory effect on spoilage bacteria. As the concentration of GEO nanoemulsion increases, the inhibitory effect increases significantly. Especially when the concentration of GEO nanoemulsion reaches 20%, the membrane has a good inhibitory effect on the growth of hyphae and spores. Figure 6 As shown in B and C, compared with the blank filter paper, C / SC / TA / O 20 The membrane significantly inhibited the growth of mycelium, and the size of mycelium inhibition was about 50.27mm 2 . C / SC / TA / O 10 The inhibitory effect of the membrane on mycelium also reached 17.62mm 2 The above results further illustrate that GEO is the reason why the composite membrane has excellent antibacterial effect.

[0140] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a ginger essential oil nanoemulsion composite film, characterized in that: The steps include: (1) Preparation of ginger essential oil nanoemulsion The ginger essential oil is added into water, and an emulsifier is added during homogenization to form a crude emulsion; the crude emulsion is crushed to obtain a ginger essential oil nanoemulsion; (2) Preparation of chitosan / sodium caseinate mixture Chitosan is dissolved in glacial acetic acid solution and stirred to obtain a completely dispersed chitosan solution; sodium caseinate is dispersed in distilled water under stirring and continuously stirred to obtain a sodium caseinate solution; the two solutions are mixed and stirred to obtain a chitosan / sodium caseinate mixed solution; (3) Preparation of ginger essential oil nanoemulsion composite film The ginger essential oil nanoemulsion obtained in step (1) is added to the chitosan / sodium caseinate mixed solution obtained in step (2) and stirred; tannic acid is then added and stirred; finally, a plasticizer is added, stirred, and ultrasonic degassing is performed to obtain a film-forming solution of a ginger essential oil nanoemulsion composite film.

2. The method for preparing the ginger essential oil nanoemulsion composite film according to claim 1, wherein: The amount of ginger essential oil added in step (1) is calculated based on its concentration in the system of 2±0.5w / v%; The emulsifier described in step (1) is Tween 80; The mass ratio of the emulsifier to the ginger essential oil in step (1) is 1:2 to 1:4; The amount of chitosan added in step (2) is calculated based on its concentration in the chitosan solution being 1±0.5 w / v%; The amount of sodium caseinate added in step (2) is calculated based on its concentration in the sodium caseinate solution of 2±0.5 w / v%; The volume ratio of the chitosan solution to the sodium caseinate solution in step (2) is 1:2 to 2:

1.

3. The method for preparing the ginger essential oil nanoemulsion composite film according to claim 2, wherein: The amount of ginger essential oil added in step (1) is calculated based on its concentration in the system of 2 w / v%; The mass ratio of the emulsifier to the ginger essential oil in step (1) is 1:3; The amount of chitosan added in step (2) is calculated based on its concentration in the chitosan solution being 1 w / v%; The glacial acetic acid in step (2) is a glacial acetic acid solution with a concentration of 1±0.5w / v%; The amount of sodium caseinate added in step (2) is calculated based on its concentration in the sodium caseinate solution being 2 w / v%; The volume ratio of the chitosan solution to the sodium caseinate solution in step (2) is 1:1; The homogenization treatment described in step (1) is achieved by a high-speed shearing machine under the following conditions: speed 12000±1000rpm, time 2±0.5min; The disruption described in step (1) is achieved by an ultrasonic cell disruptor under the following conditions: ice water bath, power 400±50w, ultrasonic time for a total of 12min, continuous 4±1s, interval 4±1s.

4. The method for preparing the ginger essential oil nanoemulsion composite film according to claim 1, characterized in that: The amount of the ginger essential oil nanoemulsion added in step (3) is calculated based on its concentration in the system of 10 v / v% to 20 v / v%; The amount of tannic acid added in step (3) is calculated based on its concentration in the system of 0.5±0.1 w / v%; The plasticizer described in step (3) is glycerol; The amount of the plasticizer added in step (3) is calculated as 30% of the total mass of sodium caseinate and chitosan.

5. The method for preparing the ginger essential oil nanoemulsion composite film according to claim 4, characterized in that: The amount of the ginger essential oil nanoemulsion added in step (3) is calculated based on its concentration in the system being 20 v / v%; The amount of tannic acid added in step (3) is calculated based on its concentration in the system being 0.5 w / v%; The amount of the plasticizer added in step (3) is calculated as 30% of the total mass of sodium caseinate and chitosan; The stirring time in step (3) is 30±5 min; The time of ultrasonic degassing described in step (3) is 30±5min.

6. The method for preparing the ginger essential oil nanoemulsion composite film according to any one of claims 1 to 5, characterized in that: In step (3), after obtaining the film-forming liquid of the ginger essential oil nanoemulsion composite film, the film-forming liquid is poured into a mold, dried and peeled off, thereby obtaining the ginger essential oil nanoemulsion composite film.

7. A ginger essential oil nanoemulsion composite film, characterized in that: The method is obtained by the preparation method described in any one of claims 1 to 6.

8. Use of the ginger essential oil nanoemulsion composite film according to claim 7 in fruit preservation.

9. The use according to claim 8, characterized in that: The application is to spray the film-forming liquid of the ginger essential oil nanoemulsion composite film on the surface of the fruit, dry it naturally to form a film on the surface of the cherry tomatoes, and preserve it.

10. The use according to claim 8, characterized in that: The fruit is cherry tomatoes; The maximum storage period is 15 days.